2023
DOI: 10.1021/acs.jafc.3c00002
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor AhR Regulates Glutathione S-Transferases Conferring Resistance to lambda-Cyhalothrin in Cydia pomonella

Abstract: Aryl hydrocarbon receptor (AhR) enhances insect resistance to insecticides by regulating the detoxification network. Our previous studies have confirmed that overexpressions of cytochrome P450 monooxygenases (P450s) and glutathione S-transferases (GSTs) are involved in lambda-cyhalothrin resistance in Cydia pomonella. Here, we report that CpAhR regulates the expression of GST and P450 genes, thus conferring resistance. Expression patterns indicated that the expression of CpAhR was highly induced by lambda-cyha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Following the injection of dsCpGPCR70, an assessment was conducted on the expression levels of detoxification genes, specifically selected as potential candidate genes known to play a role in the metabolic of lambda -cyhalothrin in C. pomonella . The result showed a notable decrease in mRNA levels of CpGSTs2 (Figure A) and CpCYP9A121 (Figure B) subsequent to the interference caused by CpGPCR70 , in comparison with the control group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the injection of dsCpGPCR70, an assessment was conducted on the expression levels of detoxification genes, specifically selected as potential candidate genes known to play a role in the metabolic of lambda -cyhalothrin in C. pomonella . The result showed a notable decrease in mRNA levels of CpGSTs2 (Figure A) and CpCYP9A121 (Figure B) subsequent to the interference caused by CpGPCR70 , in comparison with the control group.…”
Section: Resultsmentioning
confidence: 99%
“…As a control, an equal amount of dsGFP was also injected. The method of RNA interference (RNAi) has been established and applied in our laboratory . Immediately after injection, the samples were collected and promptly treated with liquid nitrogen and subsequently stored at −80 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous evidence confirmed that transcription-factor-medicated upregulation of P450 genes resulted in resistance to neonicotinoid insecticides. For instance, transcription factors CncC/Maf, CREB, HNF4, and AhR/ARNT have been proven to participate in the regulation of P450 genes mediating imidacloprid susceptibility in insects. ,,, AP-1 protein was shown to mediate clothianidin resistance by regulating CYP6ER1 in N. lugens .…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the bHLH-PAS superfamily, it has been reported that AhR/ARNT regulated the cooperative expression between CYP6CY3 and CYP6CY4 genes, conferring the nicotine adaption of Myzus persicae nicotianae to tobacco . AhR regulated the expression of GSTe3 , CYP9A121 , and CYP9A122 , thus conferring lambda-cyhalothrin resistance in Cydia pomonella . AhR and ARNT in N.…”
Section: Introductionmentioning
confidence: 99%